(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
During the last two decades the alignment of business and IT progressively occupies the attention of companies and is frequently stated as the key question and a challenge for the improvement of business and achieving success. In the beginning they were observed mainly as a support in administering the tasks and conducting defined business strategy, nevertheless, with daily development of new and improvement of the existing technologies, their impact was constantly increasing. Nowadays, they commonly represent the driving force of change in organizations and the aspect which has a significant influence on conceiving the business strategy itself. The relevant research is chiefly focused on advantages, challenges and models for achieving the IT business alignment. Conversely, they neglect the details of specific technologies that lead to changes and the need to harmonize business strategy and organizational infrastructure and processes on the one hand and IT strategy and IT infrastructure and processes on the other. A small number of papers talk about the application of certain technology and its effects on the business of companies. Therefore, the aim of this paper is to, through the overview of relevant literature, determine and make conclusions about how the utilization of new technologies influences the change and alignment of business and IT in companies. Technologies whose effects will be in focus of this research are: Big data; Internet of Things (IoT) and Blockchain.